Inoculation with Azospirillum combined with nitrogen fertilization in sorghum intercropped with Urochloa in off-season - Soares, Deyvison De Asevedo [UNESP]; Andreotti, Marcelo [UNESP]; Nakao, Allan Hisashi [UNESP]; Modesto, Viviane Cristina [UNESP]; Dickmann, Lourdes [UNESP]; Freitas, Leandro Alves (FapUNIFESP (SciELO), 2022)
The objective of this work was to evaluate the management of nitrogen fertilization in grains of sorghum inoculated or not with Azospirillum brasilense in single crop or intercropped with Urochloa brizantha (cv. Paiaguas) in the offseason. The experimental design was a completely randomized block design with four replications, in a 2 x 2 x 3 factorial scheme, with sorghum in single-cropped system or intercropped with grass; sorghum seeds inoculated or not with A. brasilense; and N management (application of 100% of the dose at sowing or only in topdressing or split -30% at sowing and 70% in topdressing) at a dose of 120 kg ha-1 N. Morphological components and sorghum grain yield and productivity of dry matter of the aerial part of the grass and the sorghum were evaluated. The splitting of nitrogen fertilization did not interfere in the yield of sorghum grain straw intercropped with U. brizantha. The intercropping with U. brizantha did not reduce sorghum grain yield. In dry climate conditions in the off-season, inoculation of sorghum seeds cv. Ranchero with A. brasilense increases grain yield.
Keywords: dizatrophic bacteria; nitrogen; paiaguas grass; Sorghum bicolor